2006
DOI: 10.1111/j.1365-2486.2006.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Sediment respiration and lake trophic state are important predictors of large CO2 evasion from small boreal lakes

Abstract: We show that sediment respiration is one of the key factors contributing to the high CO 2 supersaturation in and evasion from Finnish lakes, and evidently also over large areas in the boreal landscape, where the majority of the lakes are small and shallow. A subpopulation of 177 randomly selected lakes (o100 km 2 ) and 32 lakes with the highest total phosphorus (P tot ) concentrations in the Nordic Lake Survey (NLS) data base were sampled during four seasons and at four depths. Patterns of CO 2 concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
248
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(272 citation statements)
references
References 59 publications
(128 reference statements)
22
248
1
1
Order By: Relevance
“…Decomposition of terrestrial C is the primary source of CO 2 in Finnish lakes during winter before ice melt (Kortelainen et al 2006). Vesterinen et al (2016) reported very high littoral primary production and biomass development by the periphyton in Mekkojärvi throughout the summer of 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Decomposition of terrestrial C is the primary source of CO 2 in Finnish lakes during winter before ice melt (Kortelainen et al 2006). Vesterinen et al (2016) reported very high littoral primary production and biomass development by the periphyton in Mekkojärvi throughout the summer of 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous processes were found to proceed faster in small aquatic systems than in larger ones. Sequestration rates of organic carbon (Downing, 2010;Downing et al, 2008), the concentrations of CH 4 , CO 2 , and dissolved organic carbon (DOC) in the water column (Bastviken et al, 2004;Juutinen et al, 2009;Kelly et al, 2001;Kortelainen et al, 2006;Xenopoulos et al, 2003), and CH 4 and CO 2 emissions from the water to the atmosphere increase with decreasing lake size (Juutinen et al, 2009;Kortelainen et al, 2006;Michmerhuizen et al, 1996;Repo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, thermal stratification determining vertical mixing plays a crucial role in regulating flux of CO 2 at the water-air interface in summer. A study examining Scandinavian lakes also suggests the importance of sediment respiration as a source of CO 2 supersaturation at the surface water (Kortelainen et al 2006). Relatively high pCO 2 values in shallow isothermal lakes support an empirical model proposed by den Heyer and Kalff (1998), who suggest that contribution of sediment respiration to the total CO 2 production is high for shallow lakes because the lake bottom is as warm as the surface and likely receives organic matter with a high proportion of labile component, both of which increase heterotrophic activities at the sediment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, even when within-lake CO 2 production is high because of large inputs of terrigenous organic matter, pCO 2 may remain low as a result of the high consumption of CO 2 by increased primary producers due to large input of nutrients (Schindler et al 1997;del Giorgio et al 1999;Hanson et al 2003). Several studies have also implicated that the majority of consumption and decomposition of organic carbon may take place at the lake bottom (den Heyer and Kalff 1998;Jonsson et al 2003;Kortelainen et al 2006). If this is the case, pCO 2 at the surface water is likely higher for shallow well-mixed lakes than deep stratified lakes where the produced CO 2 would be confined below the thermocline during the stagnant seasons.…”
mentioning
confidence: 99%